2013
DOI: 10.1111/tbj.12222
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated Evaluation of the Results of Oncoplastic Surgery for Locally Advanced Breast Cancer

Abstract: The optimal surgical management of locally advanced breast cancer (LABC) remains undefined. The aim of the study was to obtain long-term results of oncoplastic surgery in terms of overall survival, loco-regional recurrence, and quality of life in case of LABC. Prospective cohort study enrolled 60 patients with stage III breast cancer. Forty-two (70%) patients received neo-adjuvant chemotherapy, 28 patients were considered suitable for surgery as initial treatment option. Type II oncoplastic surgery was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 35 publications
(47 reference statements)
0
49
0
1
Order By: Relevance
“…In developed countries with routine screening and awareness, breast cancer is usually detected early and presents as earlystage breast cancer. Locally advanced breast cancer (LABC), defined as primary tumor greater than 5 cm, with or without nodal involvement, only occurs in 5% to 10% of cases in developed countries (1)(2)(3)(4)(5)(6)(7). However, these numbers are much higher in the developing world due to lack of adequate screening, awareness, and accessibility to healthcare resources (1,3,4,7).…”
mentioning
confidence: 99%
“…In developed countries with routine screening and awareness, breast cancer is usually detected early and presents as earlystage breast cancer. Locally advanced breast cancer (LABC), defined as primary tumor greater than 5 cm, with or without nodal involvement, only occurs in 5% to 10% of cases in developed countries (1)(2)(3)(4)(5)(6)(7). However, these numbers are much higher in the developing world due to lack of adequate screening, awareness, and accessibility to healthcare resources (1,3,4,7).…”
mentioning
confidence: 99%
“…Three cases had surgical complications in our study with delay in the adjuvant therapy in 2 cases (6%), Mazouni et al [26] reported complications rate 16.7% but most of them were minor, Bogusevicius et al [22] reported complication rate 5%, with delay in adjuvant therapy in one case.…”
Section: Discussionmentioning
confidence: 43%
“…Clough et al [21] had 4 years follow up with 9.5% LR rate. Bogusevicius et al [22] said that six patients (10%) had locoregional recurrence in mean follow up 86 months.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the wider margins enabled by OBS results in lower incidence of locoregional recurrence remains to be seen on a longer follow-up. Other studies with longer follow-up have indicated a recurrence rates of 6-10 % following OBS which is comparable to that of conventional BCS [20,21]. The study may be criticized on the aspect that it is not a prospective, randomized study; rather, it relies on comparing OBS with a retrospective cohort.…”
Section: Discussionmentioning
confidence: 99%